Ethylene in postharvest biology and technology of horilcultural crops (California : University of California, 1980)
This slides describes how ethylene plays a major role in postharvest biology and technology of fresh fruits, vegetables and ornamentals.
Keywords: Horticultural crops -- Postharvest technology